(untitled) (Journal of Scientific Research, 2025)
This article describes a novel method for locating and detecting triple line to ground (LLL-G) faults in 110 km of 132 kV transmission lines. To find the transmission line fault, the three phase system currents were first recorded at the appropriate sampling frequency. Then, the total harmonic distortion (THD) and direct current (DC) components were computed using the Fast Fourier transform (FFT). When compared to normal conditions, high values of THD and DC components have been seen in fault situations; fault has been identified as a result. The fault distance in the transmission line has been measured using spline extrapolation or linear interpolation. With this method, very encouraging outcomes have been obtained for fault assessment in transmission line.